Теоретико-методичні засади туристичного брендингу міста (на прикладі м. Львова) - Музиченко-Козловська, О. В. (Видавництво Львівської політехніки, 2015)
Визначено місце туристичного бренду у формування національного бренду. Запропоновано визначення понять “туристичний бренд” та “туристичний брендинг”. Наведено передумови розроблення та реалізації стратегічного плану туристичного брендингу міста. Визначено завдання та стратегію туристичного брендингу м. Львова. Запропоновано алгоритм формування туристичного бренду міста. Розроблено модель просування туристичного бренду міста та наведено відповідну схему. Детально сформульовано кожен з етапів стратегії просування туристичного бренду м. Львова. The place of tourism brand in the formation of a national brand. A definition of "tourism brand" and "branding tourism". An prerequisites for development and implementation of the strategic plan of the tourist city branding. Objectives and strategy for tourism branding m. Lviv. The algorithm of formation of tourist brand of the city. The model of promotion of tourist brand of the city and are relevant scheme. Formulated in detail each of the stages of the strategy to promote the tourism brand of. City. The first stage assessment made of the existing brand the city. An existing brand as a logo and slogans identified its shortcomings. Done SWOT-analysis of existing tourist brand of the city and presented the results in a table. The indexes determine the overall index attractiveness of tourist brand of the city. Defined target groups of consumers and expert survey conducted attractiveness of the brand. Lviv. A scale of evaluation. Author determined measures to increase the popularity of the brand. Lviv. Done assessment of the tourism brand. Lviv and the scheme parameters and results. In the second phase determined the content of the tourist brand the city. For this analysis conducted target audience. Defined mission and goals of the tourist brand of the city. The choice of methods tourist city branding. In the third stage plan proposed promotion of tourism brand. Lviv. The measures for the promotion of tourism brand. Lviv. Formulated stages of the network of tourist information centers. Is responsible for the promotion of tourism brand. Lviv. The measures to improve Internet resources of tourism in the city. Lvov. At the fourth stage offered from the plan brand promotion of tourism. Lviv. At the fifth stage defined measures for evaluating the effectiveness of the brand. Lviv.
Theoretical and methodological foundations tourism city branding (on the example of Lviv)
Keywords: бренд; туристичний бренд; логотип; туристичний брендинг міста; стратегія туристичного брендингу; імідж; стратегічне управління іміджем; територіальний маркетинг; brand; tourism brand; logo and branding a tourist city; the tourism strategy of branding; image; strategic image management; territorial marketing